WORKING WITH DISCIPLINARY DISCOURSES IN THE LIGHT OF SYSTEMIC FUNCTIONAL THEORY - Montemayor-Borsinger, Ann (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2009)
Genre-based approaches to working with specific disciplinary discourses are reexamined in the light of systemic functional theory. This paper discusses how the Systemic Functional Linguistics (SFL) stratified model of language is used for research writing workshops held at a physics and engineering institute where English dominates as a lingua franca. The paper gives a rationale for a pedagogy focusing on interpersonal and textual strands of meaning. It provides an explicit discussion of the way in which corpus-informed materials have been used with multidisciplinary and mixed-ability groups of scientists. Such an SFL approach to exploiting language corpora for pedagogic purposes shows the pertinence of a tripartite view of language, which provides effective means of developing key aspects of disciplinary discourses by combining subject specialist expertise in the management of content representation in specific fields (ideational meanings), with linguist expertise in evaluating language alternatives for content appraisal (interpersonal meanings) and organisation (textual meanings)